Controlled methyl-esterification of pectin catalyzed by cation exchange resin. (10th February 2016) - Peng, Xiaoxia; Yang, Guang; Fan, Xingchen; Bai, Yeming; Ren, Xiaomeng; Zhou, Yifa
Highlights: A new method is developed using cation exchange resin to methyl-esterify pectin. The method can product high DE of HG and RG-I pectin without destroying structures. Pectins with varying DE can be prepared by controlling the reaction conditions. Abstract: This study developed a new method to methyl-esterify pectin using a cation exchange resin. Homogalacturonan (HG)-type pectin (WGPA-3-HG) and rhamnogalacturonan (RG)-I-type pectin (AHP-RG) obtained from the roots of Panax ginseng and sunflower heads, respectively, were used as models. Compared to commonly used methyl-esterification methods that use either methyl iodide or acidified methanol, the developed method can methyl-esterify both HG- and RG-I-type pectins without degrading their structures via β-elimination or acid hydrolysis. In addition, by modifying reaction conditions, including the mass ratio of resin to pectin, reaction time, and temperature, the degree of esterification can be controlled. Moreover, the resin and methanol can be recycled to conserve resources, lower costs, and reduce environmental pollution. This new methodology will be highly useful for industrial esterification of pectin.